2017
DOI: 10.1097/gco.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of obesity on female fertility and the health of the offspring

Abstract: Purpose of review Obesity has reached near epidemic levels among reproductive age women with a myriad of consequences. Obesity adversely affects the maternal milieu by creating conditions that decrease fertility and increase the risk of gestational diabetes, hypertensive disease in pregnancy, fetal growth abnormalities and congenital anomalies. The effects of obesity are not limited to pregnancy. Indeed, beyond the immediate postpartum period, obese women maintain a higher prevalence of insulin resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 85 publications
1
37
0
6
Order By: Relevance
“…Additionally, obese women might have an increased requirement for certain nutrients (e.g., folic acid) known to be protective against birth defects. Associations between maternal obesity, epigenetic alterations, and congenital malformations have also been proposed [ 23 , 24 ]. Finally, also considering the father's severe obesity, the role of the epigenetic paternal profile should not be excluded [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, obese women might have an increased requirement for certain nutrients (e.g., folic acid) known to be protective against birth defects. Associations between maternal obesity, epigenetic alterations, and congenital malformations have also been proposed [ 23 , 24 ]. Finally, also considering the father's severe obesity, the role of the epigenetic paternal profile should not be excluded [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]8,27 Excess adiposity among women could lead to an increase in obesity during pregnancy, lower the reproductive success, increase infant mortality and the frequency of fetal growth abnormalities and non-communicable diseases (e.g., gestational diabetes, hypertension and cardiovascular diseases). [28][29][30] Studies reported that the prevalence of gender specific overweight and obesity was observed to be higher among women than men in India. 11,13,14,16,20 The general population trend has shown that the prevalence of overweight and obesity increased slightly over the past decade in the country, but the prevalence rate has increased in urban and in high-socio-economic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the aforementioned considerations, one of the potential windows of vulnerability linking OSA and epigenetic susceptibility determinants of later onset of disease would be the occurrence of OSA during pregnancy. To this effect, we should be aware that two-thirds of women in the United States are currently overweight or obese at the time of conception, and that pre-conception obesity is fraught with higher risk for the gestation itself and for the foetal outcomes [48][49][50][51][52] . Furthermore, paternal obesity is not without risk either 53 .…”
Section: Obstructive Sleep Apnoea During Pregnancy and Consequences Tmentioning
confidence: 99%